Human Elongation Factor 4 Regulates Cancer Bioenergetics by Acting as a Mitochondrial Translation Switch - Zhu, Ping; Liu, Yongzhang; Zhang, Fenglin; Bai, Xiufeng; Chen, Zilei; Shangguan, Fugen; Zhang, Bo; Zhang, Lingyun; Chen, Qianqian; Xie, Deyao; Lan, Linhua; Xue, Xiangdong; et al. (Cancer research (Chicago, Ill.), 2018)
Mitochondria regulate cellular bioenergetics and redox states and influence multiple signaling pathways required for tumorigenesis. In this study, we determined that the mitochondrial translation elongation factor 4 (EF4) is a critical component of tumor progression. EF4 was ubiquitous in human tissues with localization to the mitochondria (mtEF4) and performed quality control on respiratory chain biogenesis. Knockout of mtEF4 induced respiratory chain complex defects and apoptosis, while its overexpression stimulated cancer development. In multiple cancers, expression of mtEF4 was increased in patient tumor tissues. These findings reveal that mtEF4 expression may promote tumorigenesis via an imbalance in the regulation of mitochondrial activities and subsequent variation of cellular redox. Thus, dysregulated mitochondrial translation may play a vital role in the etiology and development of diverse human cancers. Significance: Dysregulated mitochondrial translation drives tumor development and progression. Cancer Res; 78(11); 2813–24. ©2018 AACR.